PENGEMBANGAN MANAJEMEN SEKOLAH BERBASIS SISTEM INFORMASI MANAJEMEN MELALUI APLIKASI MY IRSYADUL IBAD - Jaenuri; Kurniawati, Mella; Amanullah, M. Imam; Intan, Nurvani; Khaeriah, Yayang (Program Studi Manajemen Pendidikan Islam, 2023)
This study aims to analyze the implementation of an integrated information system in all schools under the Irsyadul Ibad Foundation and the impact of implementing an education management information system on student attitudes covering moral and social attitudes. This study was conducted by 6 educational units of the Irsyadul Ibad Foundation, Kab. Pandeglang Banten Province. This study uses qualitative methods with observation techniques, interviews and document studies. The results of this study illustrate that the application of the my Irsyadul Ibad education information system can assist educational institutions in assisting student learning activities, relationships with parents, tidying up the management and financial system of school units and foundations. By using this information system application, students' learning activities can be controlled by parents and their progress can be recorded in real time. The existence of this information system also makes it easier for parents to meet their financial obligations to the institution. The application of this management and administrative information system makes it easy for teachers to identify attitudes and develop students' attitudes.